Green energy consumption and economic growth in Sub-Saharan Africa: The moderating role of financial inclusion - Oluwagbenle, Sola; Olawumi, Ojo Rufus; Muse, Bernard Olagboyega; Chuba, Mathias Anebamine; Oyewole, Adesanmi Oriola (Edelweiss Applied Science and Technology, 2026)
The study examines the roles of financial inclusion as a moderating variable in driving green energy consumption and economic growth in Sub-Saharan Africa between 2000 and 2023, using Panel Autoregressive Distributed Lags and fixed effects models. The study established long-run relationships among green energy consumption (GEC), financial inclusion (FI), economic growth (RGDP), interest rate (RINTR), and exchange rate (EXCR). A Granger causality test was used to verify the direction and magnitude of causality among green energy consumption, financial inclusion, interest rate, exchange rate, and economic growth. The study revealed unidirectional causality from green energy consumption to economic growth, suggesting green energy consumption as a potential driver of economic growth in SSA. The Granger causality results indicate unidirectional causality from financial inclusion to economic growth, highlighting its importance in driving economic growth in SSA. Additionally, the interest rate Granger caused economic growth, suggesting that interest rates need to be carefully managed to balance economic growth and green energy transition in SSA. The results also confirm that fixed effects are statistically significant, indicating that country-specific factors play a crucial role. The findings suggest policymakers should consider country-specific contexts when promoting green energy consumption and financial inclusion policies to foster economic growth.